LEGALITAS PENEGAKKAN SANKSI HUKUM PIDANA PERPAJAKAN ATAS PELANGGARAN TERHADAP PAJAK BUMI DAN BANGUNAN - Sukartha, I Made; Djaja, Tanu (Jurnal HUKUM BISNIS, 2024)
Taxes are people's contributions to the state treasury based on law, so they can be imposed without receiving direct compensation. The main aim of taxes is to increase state income to improve people's welfare so that the function of tax criminal sanctions is a preventive tool so that perpetrators of tax crimes do not violate tax norms. However, in the implementation of tax collection there are always those who commit violations, such as in the case of land and building tax violations. In the law enforcement process, not everyone understands tax criminal sanctions and their legality. For this reason, this paper aims to describe the enforcement of tax criminal law sanctions and their legality. This paper uses a normative juridical method, namely through literature study with data sources in the form of statutory regulations, court decisions, as well as articles or other reading materials related to taxation with a qualitative descriptive approach and concludes the legality of enforcing tax criminal sanctions in accordance with the Law on General Provisions and Procedures. Taxation Number 28 of 2007. The two witnesses provided to Taxpayers to comply with tax obligations because the law enforcement process for violations of Land and Building Tax is in accordance with the legal provisions regulated in the Law. Keywords: Law Enforcement, Legal Sanctions, Legality of law, Tax Law